A Study on the Epidemiological-Molecular Role of Staphylococcus aureus Strains in the Development of Ventilator-Associated Pneumonia in a Tertiary Hospital in Brazil - Bonesso, Mariana Fávero [UNESP] (2023)
This study aimed to explore the molecular epidemiology of Staphylococcus aureus isolated from patients on mechanical ventilation and the participation of virulence factors in the development of ventilator-associated pneumonia (VAP). A prospective cohort study was conducted on patients under mechanical ventilation, with periodic visits for the collection of tracheal aspirates and clinical data. The S. aureus isolates were analyzed regarding resistance profile, virulence, expression of protein A and alpha-toxin using Western blot, clonal profile using PFGE, sequence type using MLST, and characterization and quantification of phenol-soluble modulins. Among the 270 patients in the study, 51 S. aureus strains were isolated from 47 patients. The incidence density of S. aureus and MRSA VAP was 2.35/1000 and 1.96/1000 ventilator days, respectively; of these, 45% (n = 5) were resistant to oxacillin, with 100% (n = 5) harboring SCCmec types II and IV. The most frequent among the tested virulence factors were icaA, hla, and hld. The clonal profile showed a predominance of sequence types originating from the community. Risk factors for VAP were the presence of solid tumors and the sea gene. In conclusion, patient-related risk factors, together with microbiological factors, are involved in the development of S. aureus VAP, which is caused by the patient’s own strains.